2018
DOI: 10.1111/ecc.12960
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cervical and breast cancer risk factors in women and their screening behaviours

Abstract: Breast cancer and cervical cancer are important causes of cancer‐related mortality in women all over the world. The present study was conducted in order to investigate the distribution of cervical and breast cancer risk factors in women and their knowledge and behaviours about cancer screening methods. The study is cross‐sectional in nature. It was conducted with the participation of 1,886 women in Turkey. Data were collected through a questionnaire. The knowledge and behaviours of women aged 40 and over about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
1
11
0
8
Order By: Relevance
“…By referring to the risk factors possessed by FGD members, it is necessary to carry out interventions to change their lifestyle, especially for modifiable risk factors. Each Kelurahan has different risk factors, so the intervention is adjusted to the risk factors possessed by each member of the FGD [7]. This process requires consistency and commitment from each FGD member.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By referring to the risk factors possessed by FGD members, it is necessary to carry out interventions to change their lifestyle, especially for modifiable risk factors. Each Kelurahan has different risk factors, so the intervention is adjusted to the risk factors possessed by each member of the FGD [7]. This process requires consistency and commitment from each FGD member.…”
Section: Resultsmentioning
confidence: 99%
“…These risk factors cannot be avoided and changed because it is a life process that has passed and becomespart of their history. In different studies on breast cancer and cervical cancer found that the most notable breast and cervical cancer risk factors as low education levels, high number of deliveries, short breastfeeding period, obesity and low socio-economic level [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literatürde meme ve serviks kanser taramalarına katılım durumunu düşük eğitim düzeyinin, yüksek doğum sayısının, düşük sosyoekonomik seviyenin, korku ve utanmanın olumsuz etkilediği bulunmuştur (15)(16)(17). Kırsal bölgede yaşayanların meme ve serviks kanseri taramalarına katılımının kentsel bölgeye göre daha düşük olduğu bulunmakla birlikte sağlığın sosyal belirleyicilerinin burada da etkili olduğu görülmektedir (18).…”
Section: öZunclassified
“…Determinants of screening can be culturally specific; previous work from Turkey, for example, has shown poor uptake of screening behaviours and knowledge of benefits, even in health workers (Erdem & Toktaş, ). A further study from Turkey, in this issue, Karadag Arli, Bakan, and Aslan () examined rates of breast self‐examination and found a close correlation with health literacy; this adds to a growing body of evidence compelling us to focus awareness‐raising effort about breast and cervical screening on low health literacy groups.…”
mentioning
confidence: 95%